(untitled) (The Strategic Review for Southern Africa, 2021)
African countries have warmed up to foreign direct investment (FDI) in the past two decades. In an attempt to attract more FDI, most countries have reformed their FDI policies and institutions. However, the national structures governing FDI have not been studied in-depth. This policyscience research uses a unique conceptual framework and an institutionalist approach to expose and critique national policies and institutions for FDI in Africa. The current African structures governing FDI reflect a messy web, difficult to decipher and inadequate to form a foundation for a continental regime. Policy learning and structural convergence may be essential for better FDI governance.